Empagliflozin Inhibits Hepatic Gluconeogenesis and Increases Glycogen Synthesis by AMPK/CREB/GSK3β Signalling Pathway - Yu, Xiaochen; Meng, Ziyu; Fang, Ting; Liu, Xiaohuan; Cheng, Ying; Xu, Linxin; Liu, Xiangyang; Li, Xiaoyu; Xue, Mei; Li, Ting; Sun, Bei; Chen, Liming (Frontiers in Physiology, 2022)
Increases in glucose production and decreases in hepatic glycogen storage induceglucose metabolic abnormalities in type 2 diabetes (T2DM). Empagliflozin, a sodium-dependent glucose transporter 2 (SGLT2) inhibitor, is an effective hypoglycaemic drug; however, the effects of empagliflozin on hepatic gluconeogenesis and glycogenesis are still unclear. In this study, we investigated the effects and mechanisms of empagliflozin on hepatic gluconeogenesis and glycogenesis in vivo and in vitro. Empagliflozin was administered via gavage to db/db mice for eight weeks, and human hepatocytes HL7702 cells were treated with empagliflozin after palmitic acid (PA) stimulation. Compared with the control db/db mice, empagliflozin-treated mice showed significant reduction in urine glucose levels, blood glucose levels, body weight and intraperitoneal glucose tolerance tests (IPGTT) blood glucose levels. Moreover, the expression levels and activities of key gluconeogenesis enzymes PEPCK and G6Pase were dramatically reduced in the empagliflozin-treated mice and the protein expression levels of AMPK/CREB/GSK3β signalling pathway-related molecules were significantly changed. In the HL7702 cells, empagliflozin ameliorated glucose production and PEPCK and G6Pase expression and activity. Empagliflozin could also prevent the decreases in glycogen content and regulate the protein expression levels of AMPK/CREB/GSK3β signalling pathway-related molecules. Then, we selected the AMPK agonist AICAR and inhibitor Compound C to further verify the effects of the AMPK signalling pathway on hepatic gluconeogenesis and glycogen synthesis. The results of the AIACR intervention in HL7702 cells were consistent with those of the empagliflozin treatment, and the effects of empagliflozin were abolished by Compound C. In summary, empagliflozin could maintain glucose homoeostasis by reducing gluconeogenesis and increasing glycogenesis through the AMPK/CREB/GSK3β signalling pathway.